2020
DOI: 10.1186/s12885-020-06909-y
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic alterations of genome and transcriptome in KRAS G13D mutant CRC PDX model treated with cetuximab

Abstract: Background: KRAS mutations have been characterized as the major predictive biomarkers for resistance to cetuximab treatment. However, studies indicate that not all KRAS mutations are associated with equivalent treatment outcomes. KRAS G13D mutations were observed to account for approximately 16% of all KRAS mutations in advanced colorectal cancer patients, and whether these patients can benefit from cetuximab has not been determined. Methods: An established KRAS G13D mutant colorectal cancer (CRC) patient-deri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…After repeated treatment tumor acquired resistance to cetuximab, and significant changes were identified in JAK2, PRKAA1, FGFR2, and RALBP1 expression. In particular, SWAP70 , related to tumor development, may be a probable gene involved in cetuximab resistance in KRAS G13D CRC [ 110 ].…”
Section: Patient-derived Modelsmentioning
confidence: 99%
“…After repeated treatment tumor acquired resistance to cetuximab, and significant changes were identified in JAK2, PRKAA1, FGFR2, and RALBP1 expression. In particular, SWAP70 , related to tumor development, may be a probable gene involved in cetuximab resistance in KRAS G13D CRC [ 110 ].…”
Section: Patient-derived Modelsmentioning
confidence: 99%
“…In the CRC first-line chemotherapy, anti-EGFR monoclonal antibodies have been clinically and statistically confirmed less effective when treating patients with RAS and BRAF mutations ( 7 , 8 , 28 , 29 ). However, quite a few studies supported that cetuximab might be effective in KRAS G13D mutation (accounts for approximate 16% of all KRAS mutations) ( 30 , 31 ). In terms of the microsatellite instability, a recent study implied that cetuximab could even promote disease progression in stage III colon cancer patients with deficient mismatch repairing ( 5 ).…”
Section: Discussionmentioning
confidence: 99%
“… 120 A recent study reported the dynamic alterations of biomarkers in KRAS G13D mutant CRC PDX model treated with cetuximab. 121 The expression of EGFR ligands is associated with the sensitivity of CRC to cetuximab, and the gene copy number of some oncogenes ( BRAF , EGFR , and KRAS ) is correlated positively with cetuximab and erlotinib sensitivity. 120 , 122 The implementing systems and molecular images were established to predict the efficacy of BCL‐2 inhibition in CRC based on a PDX cohort.…”
Section: The Application Of Pdx In Crc Researchmentioning
confidence: 99%
“…Moreover, the downregulation in classical EGFR‐mediated signaling and the upregulation in antiapoptotic signaling are associated with acquired cetuximab resistance 120 . A recent study reported the dynamic alterations of biomarkers in KRAS G13D mutant CRC PDX model treated with cetuximab 121 . The expression of EGFR ligands is associated with the sensitivity of CRC to cetuximab, and the gene copy number of some oncogenes ( BRAF , EGFR , and KRAS ) is correlated positively with cetuximab and erlotinib sensitivity 120,122 .…”
Section: The Application Of Pdx In Crc Researchmentioning
confidence: 99%